2009
DOI: 10.1007/s10533-009-9316-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate sources and watershed denitrification inferred from nitrate dual isotopes in the Beijiang River, south China

Abstract: The great spatial and temporal variability of nitrogen (N) processing introduces large uncertainties for quantifying N cycles in large scales, e.g. a watershed scale, and hence challenges the present techniques in measuring ecosystem N mass balance. The dual isotopes of nitrate (d 18 O and d 15 N) integrate signals for both nitrate sources and N processing, making them promising for studies on large scale N cycling. Here, the dual isotopes, as well as some ion tracers, from a subtropical river in south China w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 52 publications
5
104
1
4
Order By: Relevance
“…When compared with the TN concentrations of rivers and lakes in the Beijing metropolitan area in 2003, at which point they were all below 2 mg $L -1 [17], TN concentrations showed an increasing trend. The TN concentrations reported in this study are higher than those in the Taihu lake region [26], in the Haicheng river basin [27]and in the Beijiang river in south China [28], but close to the TN level of the Thames river in the UK [29], and of stream water in Pennsylvania, USA [30]. These increasing TN concentrations may be due to intensification of human activities caused by urbanization, and agrees with other studies which have shown that urbanization results in elevated TN and NO -3 -N concentrations in watersheds in developing areas [31,32], and that urbanization soon takes over as the major source of nitrogen in urban freshwater ecosystems [27].…”
Section: Characteristics Of Nitrogen Pollutioncontrasting
confidence: 53%
“…When compared with the TN concentrations of rivers and lakes in the Beijing metropolitan area in 2003, at which point they were all below 2 mg $L -1 [17], TN concentrations showed an increasing trend. The TN concentrations reported in this study are higher than those in the Taihu lake region [26], in the Haicheng river basin [27]and in the Beijiang river in south China [28], but close to the TN level of the Thames river in the UK [29], and of stream water in Pennsylvania, USA [30]. These increasing TN concentrations may be due to intensification of human activities caused by urbanization, and agrees with other studies which have shown that urbanization results in elevated TN and NO -3 -N concentrations in watersheds in developing areas [31,32], and that urbanization soon takes over as the major source of nitrogen in urban freshwater ecosystems [27].…”
Section: Characteristics Of Nitrogen Pollutioncontrasting
confidence: 53%
“…Concentrations sharply increased from low values to values well over 15 mg·L −1 , after which the concentration decreased in a downstream direction until it almost zero downstream. The fact that this decline was accompanied by a consistent increase in the 15 N isotope abundance in the pool NO 3 -N identifies that nitrate loss is due to denitrification to nitrogen gas, rather than from dilution [7,35,37,45]. In the model, the decline of nitrate was reproduced with a first-order nitrate consumption rate of 1 kg day −1 , again comparable to parameters often used in sediment models (e.g., 0.2-3.5 kg·day −1 ) [46].…”
Section: Inorganic N In Surface Watersmentioning
confidence: 96%
“…Finally, the ∂ r values are transformed to percentages (%) to obtain the degree of denitrification for each sampling point [37]. To calculate the degree of denitrification from our data, the initial isotopic composition (∂ r0 ) was chosen to be the lowest 15 N value during the samplings.…”
Section: Stable Isotope Calculationsmentioning
confidence: 99%
See 2 more Smart Citations